2016
DOI: 10.1080/00332747.2015.1123593
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder, Hostile Cognitions, and Aggression in Iraq/Afghanistan Era Veterans

Abstract: OBJECTIVE Though most veterans with Posttraumatic Stress Disorder (PTSD) are not violent, research has demonstrated that there is substantial minority who are at increased risk. This study tested hypotheses regarding hyperarousal symptoms and hostile cognitions (i.e. “hostility”) as potential mechanisms of the association between PTSD and physical aggression in a longitudinal sample of Iraq/Afghanistan era veterans. METHOD U.S. veterans between the ages of 18 and 70 who served in the military after September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Research has linked hostility in individuals with PTSD to physiological hyperarousal (Beckham et al, 2009, 2002; Vrana et al, 2009), and improved arousal regulation has been found to be the one of the primary mechanisms of change in anger management therapy for veterans with PTSD (Mackintosh et al, 2014a, 2014b). Considered in the context of these prior studies, our findings may suggest that directly targeting the PTSD-related physiological arousal (Beckham et al, 2009, 2002; Dennis et al, 2016, 2017; Mackintosh et al, 2014a, 2014b; Vrana et al, 2009) and hostile cognitions (Van Voorhees et al, 2016) that contribute to irritability and anger may be an important part of a holistic approach to minimizing the functional impact of the disorder. Current empirically support therapies specifically target the avoidance symptoms that are understood to maintain PTSD (Cahill et al, 2003; Foa et al, 2006; Resick et al, 2010), while less attention is given to directly targeting physiological arousal and hostile interpersonal attributions cued by trauma triggers.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Research has linked hostility in individuals with PTSD to physiological hyperarousal (Beckham et al, 2009, 2002; Vrana et al, 2009), and improved arousal regulation has been found to be the one of the primary mechanisms of change in anger management therapy for veterans with PTSD (Mackintosh et al, 2014a, 2014b). Considered in the context of these prior studies, our findings may suggest that directly targeting the PTSD-related physiological arousal (Beckham et al, 2009, 2002; Dennis et al, 2016, 2017; Mackintosh et al, 2014a, 2014b; Vrana et al, 2009) and hostile cognitions (Van Voorhees et al, 2016) that contribute to irritability and anger may be an important part of a holistic approach to minimizing the functional impact of the disorder. Current empirically support therapies specifically target the avoidance symptoms that are understood to maintain PTSD (Cahill et al, 2003; Foa et al, 2006; Resick et al, 2010), while less attention is given to directly targeting physiological arousal and hostile interpersonal attributions cued by trauma triggers.…”
Section: Discussionmentioning
confidence: 82%
“…However, it may be that even relatively small increases in the proportion of time spent coping with anger-related affect could have a significant impact on interpersonal functioning, physical health, and overall sense of well-being. On an interpersonal level, heightened levels of negative affective arousal in response to day-to-day exposure to emotionally distressing trauma cues may underlie the increased risk for infrequent (but often socially and interpersonally devastating) verbal or physical aggression that has been observed in individuals with PTSD (Elbogen et al, 2012, 2014a, 2014b; Miles et al, 2015a, 2015b; Van Voorhees et al, 2016). People with PTSD who experience anger often report that they avoid interpersonal engagement as much as possible in an effort to prevent such undesirable outcomes (Frueh et al, 1997; Miles et al, 2015a, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Aggression is greatly influenced by experience. Prior agonistic or stressful experience can be a predictor for aggression symptoms associated with psychiatric disorders, such as PTSD and intermittent explosive disorder (Nelson and Trainor, 2007;Van Voorhees et al, 2016;Taft et al, 2017). The neural mechanism underlying experience-dependent modification of aggression, however, remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are several risk factors that have been consistently shown to be associated with an increased prevalence of violent behavior among veterans and service members. These include the number of deployment-related traumas, PTSD diagnosis, alcohol abuse, and combat exposure (Elbogen, Johnson, Newton, et al, 2012; Elbogen, Wagner, et al, 2010; Gallaway et al, 2012; Macmanus et al, 2012; Macmanus et al, 2013; Miles, Menefee, Wanner, Teten Tharp, & Kent, 2016; Shin, Rosen, Greenbaum, & Jain, 2012; Thomas et al, 2010; Van Voorhees et al, 2016). In addition, factors associated with lower risk for violent behavior among Iraq and Afghanistan veterans include income level, psychosocial factors like social support, and physical health (Elbogen, Johnson, Wagner, et al, 2012; Elbogen, Wagner, et al, 2010; Shin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%